Assessment of knowledge, attitude and practice about biomedical waste management among healthcare staff of Fasa educational hospitals in COVID-19 pandemic. (December 2022) - Shekoohiyan, Sakine; Parsaee, Fatemeh; Ghayour, Sara
Abstract: An efficient management of biomedical waste (BMW) is essential to maintaining health and preventing environmental threats during the COVID-19 pandemic. Thus, the present research aimed to explore the knowledge, attitude, and practice about BMW among the healthcare staff of Fasa educational hospitals. The present cross-sectional study used an online questionnaire survey to collect data from 251 employees in Valiasr and Shariati hospitals in 2021. T -test, ANOVA, and Pearson correlation coefficient were used to test the relationships between and among the variables. Demographic findings showed that the men and women participated to an almost equal rate. Most participants were young and had less than 5 years' work experience. Their mean scores of knowledge, attitude, and practice were 38.8±6.1, 83.0±8.8, and 47.5±14.5, respectively. These values point to a satisfactory level of each variable in relation to BMW management. Pearson's correlation coefficient test showed a strong positive association between knowledge and practice (r = 0.725). The T -test results showed a statistically significant relationship among knowledge, attitude, and practice across demographic variables. These included gender, ward (COVID vs. Non-COVID), and workplace (p < 0.05). ANOVA results showed statistically significant divergences in knowledge, attitude, and practice across the demographic variables, including education, position, and employment type (p < 0.05). Considering the current deficiencies among employees in terms of BMW acronyms, lack of waste training courses, and inappropriate waste plans for COVID-19 waste management, BMW training courses should be held continuously and regularly, and the content of the programs should be updated according to the emergencies.